THEORETICAL AND PRACTICAL ASPECTS OF INTRODUCTION OF THE COMBINED TEACHING OF HIGHER MATHEMATICS ARE IN HIGHER EDUCATIONAL MARINE ESTABLISHMENTS (Journal of Information Technologies in Education (ITE), 2012)
In the article essence of concept «blended learning» is reasonable in theory. The features of organization of the combined educating are considered in higher marine educational establishment.
Keywords: e-learning; methods of educating; of informatively-communication technologies; the combined educating